THE FORMULATION AND SENSORY ASSESSMENT OF VALUE-ADDED FLAVORED PANEER, ENRICHED WITH A NEWLY DEVELOPED NUTRITIONAL SUPPLEMENT, REVEALED AN INNOVATIVE APPROACH TO ENHANCING BOTH TASTE AND HEALTH BENEFITS IN DAIRY PRODUCTS. - Priyanka Kushwaha* and Devendra Kumar Bhatt** (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Strengthening is one of the finest ways to meet the nutritional demands of the people and increase immunity. The public strongly supports this excellent public health strategy. Lotus stems, also referred to as Kamal Kakudi in the local dialect, are rich in minerals, including 60.6 mg of iron, 405 mg of calcium, and 128 mg of phosphorus. They also include two antioxidants, catechin and gallocatechin, which have the potential to have immunomodulatory and antiviral properties. As a plentiful source, soybean (Glycine max.) is rich in antioxidants, omega-3 fatty acids and other healthful substances like phytosterols, lecithin and phenolic acids. It also contains 40% protein of high biological value and essential amino acids, specifically glycine, tryptophane and lysine as well as a reasonable amount of minerals, vitamins and dietary fibre. Fat, fibre, protein, minerals and vitamins including ascorbic acid, thiamine, riboflavin and β-carotene are all found in moringa leaves. Quercetin, a chemical found in Moringa oleifera leaves, inhibits the growth of cancerous cell in humans. The goal of the current study is to evaluate the general acceptability and sensory quality of many sample of flavored paneer that are supplemented with NDS at ratio of 5%, 10%, 15% and 20%. A 9 point Hedonic rating test was used to assess the sensory qualities of flavored paneer including appearance, texture, color, after taste and overall acceptability by 60 panelists (36 male and 24 female). As for sensory acceptability in term of appearance, treatment 3 has the highest acceptability (43.33%) and treatment 4 has the lowest acceptability (13.34%). The majority of acceptability was observed for treatment 3 (63.33%- Like Extremely), which was followed by treatment 2 (55%- Like Very Much), treatment 1 (45%- Like moderately) and treatment 4 (33.33%- Like very much). Treatment 3 has the maximum acceptance (33.33%) in term of color, whereas treatment 4 has the lowest acceptability (16.66%). Treatment 2 had the highest percentage (30%) of texture acceptability, whereas treatment 3 had the best acceptability of flavor and after taste (35% flavor and 33.33% after taste). Out of all the treatment, treatment 3 had the greatest overall acceptance rate (45%), while treatment 4 had the lowest overall acceptability rate (13.34%).